Discovery Learning Method in Improving Learning Outcomes of Islamic Religious Education (A Study at SMKN 1 Baubau) - Wa Darma (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2022)
This research aims to improve student learning outcomes in the material Modeling the Struggle of the Prophet's Da'wah in Mecca through the Discovery Learning method in class X BDP 3 SMKN 1 Baubau for the 2022 academic year.This type of research is classroom action research conducted in class at SMKN 1 Baubau in the odd semester of the 2022/2023 academic year with a total of 38 students. The factors examined in this study were (1) learning outcomes factors, (2) teacher factors, and (3) student factors. This research was carried out in 2 cycles with implementation procedures (1) planning, (2) implementing actions, (3) observation, and (4) analysis and reflection. The research data were analyzed using descriptive statistics. The indicators of the success of this research are (1) in terms of process, that is, actions are categorized as successful if at least 85% of the learning scenarios are carried out well, and (2) in terms of results, that is, an action is categorized as successful if at least 85% of students have obtained a score of ≥ 70 in accordance with the KKM for Islamic Education and Moral Education for class X BDP 3 SMKN 1 Baubau for the 2022/2023 academic year. The results of this study indicate that the application of Discovery Learning learning can improve student learning outcomes in class X BDP 3 SMKN 1 Baubau for the 2022/2023 academic year. It is seen thatbefore implementing the action of student learning outcomes with an average classical percentage of 65% increases to 76% in the implementation of Cycle I actions, and increases again to 86% in Cycle II.